2020
DOI: 10.2147/cmar.s253366
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and Safety of Anlotinib for Patients with Advanced NSCLC Who Progressed After Standard Regimens and the Preliminary Analysis of an Efficacy Predictor</p>

Abstract: Background The aim of this study was to investigate the efficacy and safety of anlotinib for patients with advanced non-small cell lung cancer (NSCLC) who progressed after standard regimens in real world situations and the preliminary analysis of an efficacy predictor. Methods A total of 118 patients with advanced NSCLC who progressed after standard regimens were included in this retrospective study. Efficacy was evaluated and toxicity profile was recorded. Progression-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…The incidence of adverse events recorded in both groups was low and similar to those reported in the literature [25,[40][41][42][43][44][45][46]. In this study, the proportion of patients rechecking ECG, thyroid function and urine routine was small.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of adverse events recorded in both groups was low and similar to those reported in the literature [25,[40][41][42][43][44][45][46]. In this study, the proportion of patients rechecking ECG, thyroid function and urine routine was small.…”
Section: Discussionsupporting
confidence: 86%
“…Anlotinib is a multitarget tyrosine kinase inhibitor that was originally designed to inhibit VEGFR2/3, FGFR1-4, PDGFRα/β, c-Kit, and Ret ( 16 ), thereby exerting inhibitory effects on tumor angiogenesis and growth ( 13 ), tumor invasion ( 17 ), lymphangiogenesis and lymphatic metastasis ( 18 ). Anlotinib has been shown to be effective in the treatment of advanced non-small cell lung cancer ( 19 ), small cell lung cancer ( 20 ), esophageal squamous cell carcinoma ( 21 ), metastatic colorectal carcinoma ( 22 ), soft tissue sarcoma ( 23 ). Anlotinib has also demonstrated a sustained antitumor activity in locally advanced or metastatic medullary thyroid carcinoma, with a PFS rate of 85.5% at 48 weeks of treatment ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…No SAEs occurred in this patient, most of which could be controlled with medication, and a few of which could disappear spontaneously, with grade 3 AEs including diarrhea, hypertension, and headache. Interestingly, hypertension was considered to be a biomarker for efficacy prediction of anlotinib in advanced NSCLC ( 19 ). Hand-foot syndrome persists and affects the patient's quality of life, and also can be relieved by taking celecoxib and applying urea-vitamin E cream.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced NSCLC, anlotinib is a small molecule multi-target tyrosine kinase inhibition of VEGFR1-3, FGFR1-4, and PDGFRα-β, among others. 18,19 It plays a crucial role as a third or further line of targeted therapy and has shown excellent e cacy in treating NSCLC during clinical trials. Anlotinib has also been associated with various adverse reactions, including hyperlipidemia among other symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 Some previous studies have demonstrated that some elements such as CD31-labled activated circulating endothelial, levels of KLK5 and L1CAM, post-treatment hyperlipidemia, post-treatment hypertension status and pre-treatment ECOG scores, might be potential biomarkers for effectively predicting anlotinib in NSCLC patients. [19][20][21][22] To date, however, these genetic and cytological factors are expensive and inconvenient to obtain, and none of these evidences have described the potential association between blood lipids before treatment and e cacy of anlotinib in treatment of NSCLC. Therefore, we analyzed differences in basal lipids levels during patient survival as well as the effective ratio, and found that these can be a signi cant predictor to guide future individualized treatment.…”
Section: Introductionmentioning
confidence: 99%